PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN LUAS WILAYAH DAERAH TERHADAP ALOKASI BELANJA MODAL STUDI EMPIRIS DI PROVINSI JAWA TIMUR - Robin Keswando, Suharno & Djoko Kristianto (Universitas Slamet Riyadi, 2016)
This research aims to see the significant impact of the original Income influence area (PAD), General Allocation Funds (DAU), Special Allocation Fund (DAK), and the regional width to the capital expenditure allocation. The research population is all over the districts and/or cities in East Java Province, in the period of 2012-2014. The number of samples used is the whole districts and/or cities in East Java Province, thus it belongs to census research. The data analysis technique used is the multiple linear regression analysis. The partial analysis result concludes that PAD and the regional width positively and significantly influence the capital expenditure allocation while DAU and DAK do not significantly influence the capital expenditure allocation. The result of the analysis simultaneously shows a conclusion that PAD, DAU, DAK, and the regional width positively and significantly influence the capital expenditure allocation. The determination coefficient analysis result obtains the Adjusted R Square value = 0,892 which shows that the influence given by the independent variables, which are PAD, DAU, DAK, and the regional width to the capital expenditure allocation is about 89,2% while the 10,8% rest is influenced by other variables outside the variables examined.Keywords: PAD, DAU, DAK, regional, capital expenditure